The Effectiveness of Ethanol Extract of Ketapang Leaves (Terminalia catappa L.) as a Larvicidal Against Aedes aegypti Mosquito Larvae - Dwi Ananda, Novita; Rachmawati, Kadek; Lastuti, Nunuk Dyah Retno; Suwanti, Lucia Tri; Hidajanti, Nove; Meles, Dewa Ketut (Universitas Airlangga, 2023)
This study aimed to determine the effectiveness of the ethanol extract of ketapang leaves (Terminalia catappa) on mortality and histopathology of Ae. aegypti instar III as an effort to control Ae. aegypti as a disease vector without causing resistance to the larvae. The extraction process uses the maceration method. This type of research is a laboratory experiment with research subjects Ae. aegypti instar III of 700 individuals, which were divided into 7 treatment groups (1 negative control group using distilled water and 1% DMSO, 1 positive control group using 1000 ppm abate, ethanol extract of ketapang leaves with concentrations of 2000 ppm, 2500 ppm, 3500 ppm, 5000 ppm, 7000 ppm) and 4 repetitions. The results of this study indicate that the negative control (K-) mortality rate is 0% and the positive control (K+) mortality percentage is 100%. The results of the ethanol extract of ketapang leaves (Terminalia catappa) on the mortality of Ae. aegypti instar III in treatment one (P1) the percentage of mortality was 17%, treatment two (P2) the percentage of mortality was 21%, treatment three (P3) the percentage of mortality was 23%, treatment four (P4) the percentage of mortality was 27%, and treatment five (P5) the percentage of mortality is 42%. Histopathological observations on larvae that died after being exposed to ethanol extract of ketapang leaves (Terminalia catappa) for 24 hours damaged the basement membrane, peritropic membrane and epithelial cells. It can be concluded that the ethanol extract of ketapang leaves (Terminalia catappa) is effective as a larvicidal against Ae. aegypti instar III but can cause damage to the midgut and cause death of the larvae.